2007
DOI: 10.1007/s10531-006-9025-x
|View full text |Cite
|
Sign up to set email alerts
|

AFLPs and morphological diversity of Phaseolus lunatus L. in Cuban home gardens: approaches to recovering the lost ex situ collection

Abstract: The genetic diversity of 76 accessions of lima bean (Phaseolus lunatus L.), collected mostly from home gardens, was assessed with AFLPs and seed descriptors to evaluate the potential for recovering a lost ex situ collection in Cuba. The sample contained 60 accessions collected from 25 home gardens in the three main geographical regions of Cuba and represented the three cultivated types found on the island. Four more accessions were part of the former ex situ collection and the remaining 12 accessions were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…A diversidade encontrada no presente estudo, em relação à morfologia das sementes, foi relatada por Castiñeiras et al (2007), que avaliaram 76 acessos de P. lunatus, e classificaram o feijão-fava em oito grupos distintos quanto ao tamanho, comprimento, largura e circunferência das sementes.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A diversidade encontrada no presente estudo, em relação à morfologia das sementes, foi relatada por Castiñeiras et al (2007), que avaliaram 76 acessos de P. lunatus, e classificaram o feijão-fava em oito grupos distintos quanto ao tamanho, comprimento, largura e circunferência das sementes.…”
Section: Resultsunclassified
“…Os marcadores moleculares permitiram identificar os acessos em três grupos de feijão-fava cultivados (Sieva, Sieva/Papa e Papa) e suas origens geográficas (norte, centro e sul), já os morfológicos permitiram separar apenas os grupos cultivados, devido à característica fenotípica ser grandemente influenciada pelo fator ambiental e grande pressão de seleção exercida pelos agricultores (Castiñeiras et al, 2007). Guimarães et al (2007) separaram 22 acessos oriundos dos Estados do Ceará, Paraíba e Pernambuco em dois grupos diferentes utilizando marcadores RAPD, já com a utilização de marcadores morfológicos, como a massa de 100 sementes não foi possível separar os acessos devido a influência ambiental e a existência de troca de sementes entre agricultores geograficamente próximos.…”
Section: Resultsunclassified
“…This difference may be due to the low representativity of the plant material used by Nienhuis et al (1995). Castiñeiras et al (2007), using AFLP molecular markers, analyzed the genetic diversity of Potato-Sieva landraces planted in the Cuban home gardens. They reported a genetic diversity (h = 0.119) similar to the one reported by Nienhuis et al (1995).…”
Section: Resultsmentioning
confidence: 99%
“…Lioi et al (1998) reported H E = 0.13 for 60 cultivated accessions that included both Mesoamerican and Andean landraces. Castiñeiras et al (2007), using AFLP markers, reported H T = 0.13 for 65 cultivated accessions from Cuba. Montero-Rojas et al (2013) reported H E = 0.337 and H O = 0.403 for 50 landraces collected directly from Haiti, Puerto Rico and the Dominican Republic.…”
Section: Genetic Relationships Among Landraces Of Lima Beanmentioning
confidence: 99%